Pengaruh Rasio Profitabilitas Terhadap Harga Saham pada Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia - Yuniza, Tri Fira (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
his study aims to determine whether the profitability ratio, namely ROA and ROE, has a positive and significant effect on shares in insurance companies listed on the Indonesia Stock Exchange.The population used to determine the effect of profitability ratios on companies incorporated in the insurance sector on the Indonesia Stock Exchange is as many as 5 companies based on information obtained from the Indonesia Stock Exchange.The results of this study indicate that changes in capital structure are not influenced by the value of the company, meaning that all capital structures are considered not good because they have no effect on the value of the company. A good capital structure if the company changes the capital structure and followed by changes in firm value, because the capital structure that can maximize the value of the company is a good capital structure.